Civic and Political Engagement during the Multifaceted COVID‐19 Crisis. Issue 2 (10th May 2021) - Borbáth, Endre; Hunger, Sophia; Hutter, Swen; Oana, Ioana‐Elena
Abstract: Measures to cope with the COVID‐19 pandemic have put a sudden halt to street protests and other forms of citizen involvement in Europe. At the same time, the pandemic has increased the need for solidarity, motivating citizens to become involved on behalf of people at risk and the vulnerable more generally. This research note empirically examines the tension between the demobilisation and activation potential of the COVID‐19 crisis. Drawing on original survey data from seven Western European countries, we examine the extent, forms, and drivers of citizens' engagement. Our findings show the remarkable persistence of pre‐existing political and civic engagement patterns. Concurrently, we show that threat perceptions triggered by the multifaceted COVID‐19 crisis have mobilized Europeans in the early phase of the pandemic. Similarly, the role of extreme ideological orientations in explaining (regular) political engagement indicates that the current situation may create its specific mobilisation potentials. Zusammenfassung: Die Massnahmen zur Bewältigung der COVID‐19 Pandemie haben Strassenprotesten und andere Formen des bürgerschaftlichen Engagements in Europa zunächst ein abruptes Ende gesetzt. Gleichzeitig hat die Pandemie den Bedarf an solidarischem Handeln erhöht und Bürger*innen dazu motiviert, sich für Risikogruppen und allgemein für Schwache einzusetzen. Diese empirische Studie untersucht das Spannungsverhältnis zwischen dem Demobilisierungs‐ und dem Aktivierungspotenzial der COVID‐19 Krise. Mittels Umfragedaten aus sieben westeuropäischen Ländern analysieren wir das Ausmass, die Formen und die Triebkräfte politischen und sozialen Engagements. Unsere Ergebnisse zeigen eine bemerkenswerte Beständigkeit bereits bestehender Muster. Gleichzeitig zeigen wir, dass durch die Vielschichtigkeit der Krise ausgelöste individuelle Bedrohungswahrnehmungen die Europäer*innen in der Frühphase der Pandemie mobilisiert haben. Ebenso besteht ein Zusammenhang zwischen radikalen ideologischen Orientierungen und (regelmässigem) politischem Engagement, der darauf hindeutet, dass die Pandemie ganz spezifische Mobilisierungspotenziale erzeugt. Résumé: Les mesures prises pour contrer la pandémie de COVID‐19 ont d'abord marqué un coup d'arrêt aux manifestations et aux autres formes de participation citoyenne en Europe. En même temps, la pandémie a renforcé le nécessité d'une solidarité plus forte, motivant les citoyens à s'engager pour les personnes à risque et les vulnérables en général. Cette note de recherche analyse la tension entre le potentiel de démobilisation et d'activation de la crise liée au COVID‐19. Sur la base de données de sondage pour sept pays d'Europe occidentale, nous examinons le degré, les formes et les motivations de la participation citoyenne. Nos résultats soulignent la persistance remarquable des modèles d'engagement politique et civique préexistants. En même temps, nous montrons que les perceptions de la menace provoquées par la crise COVID‐19 ont mobilisé les Européens dans la phase initiale de la pandémie. De même, les orientations idéologiques extrêmes expliquent l'engagement politique (régulier), ce qui indique que la situation de crise crée un potentiel de mobilisation spécifiques.